Влияние бора на процесс синтеза и свойства алмаза - Бугаков, В.И.; Поздняков, А.А.; Давыдов, В.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Experimental data on the dependence of diamond yield, fraction composition and compression strength diamond powder on the concentration boron in the starting mixture has been obtained. It has been shown that there is the possibility of using Ni2B stoichiometric composition as source boron.